Art of Reading Signs: Police Intelligence and Early Detection Strategy for Election Threat Management - Sjam, Muh. Adam; Sabir, Muhammad; Syahril, Muh. Akbar Fhad; Kairuddin, Kairuddin; Kasim, Aksah (Sekolah Tinggi Ilmu Kepolisian, 2025)
This study examines the performance of Intelligence and Security Unit of Pare-pare Police Resort in anticipating potential security threats during the 2024 Regional Elections using the early detection strategy in order to figure out the effectiveness of the strategy and its suitability with applicable provisions. Utilising both normative and empirical approach, this study analyses the laws and regulations using field observations. The findings of this research shows that the Intelligence and Security Unit has implemented a comprehensive strategy following applicable laws and regulations but it still faces challenges in the digital era. Increasing the capacity of big data analysis, social media monitoring, and information-sharing mechanisms among institutions are needed to anticipate security disturbances in the future election. This strategy has the potential to be a model for other regions in Indonesia, although it still requires continuous improvement and adaptation of technology.